Analysis of Students’ Errors in Solving Mathematical Critical Thinking Problems on Junior High School - Sodik, Rahmat; Hendriana, Heris; Supriatna, Tatang; Putra, Harry Dwi ((JIML) JOURNAL OF INNOVATIVE MATHEMATICS LEARNING, 2025)
Critical thinking ability is one of the important competencies that students must have in facing challenges in the information age. This research aims to identify the types of errors made by class VII junior high school students in solving critical thinking skills questions on algebra material. This research uses a qualitative descriptive approach with the research subjects were 32 students in class VII.7, data collection was carried out through written tests containing critical thinking questions. It was found that several students made mistakes in solving algebra material questions, namely 1) Not understanding the concept of algebra definition; (2) The settlement process is not systematic; (3) There is no resolution process, go straight to the answer; (4) Do not understand the meaning of the question; (5) Weak in analyzing and arguing (6) Difficulty modeling problems in algebraic form; (7) Not understanding how to calculate operations and the properties of algebraic operations; (8) No identification of questions, no collection and compilation of data in the questions; (9) Not familiar with complex multiple choice questions. This research shows that students' critical thinking skills in solving algebra problems are still low. This is caused by several factors, such as a lack of in-depth understanding of concepts, lack of process skills, and less effective study habits. To improve students' critical thinking abilities, improvements in learning need to be made, such as strengthening understanding of concepts, developing process skills, and improving study habits.